Letters from Sultan Ibrahim 1785-1794: Selangor Political and Economic Reflections at the End of 18th Century - Amin, Abdur-Rahman Mohamed (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
This paper analyzes the content of 47 letters sent by the Sultan of Selangor, Sultan Ibrahim, at the end of the 18th century, which form a part of 'The Light Letters' collection, with the reference number MS 40320. These jawi-written manuscripts are preserved in the Archive and Special Collections of the School of Oriental and African Studies Library at the University of London. The letters from Sultan Ibrahim were retrieved from the collection of "The Light Letters" and reorganized according to the dates listed in these letters, beginning from 1785. These letters largely display the relationship between Sultan Ibrahim and Francis Light. The analysis included the seals of the sultan, content and closing statements. The content of the letters covers politics, the economy, weaponry and the hajj pilgrimage. In summary, these letters are important as a primary reference for studying the history of Selangor at the end of 18th century because of their content that shows the political and economic situations in Selangor, based on the writings by the sultan himself. Keywords: The Light Letters, Selangor, Sultan Ibrahim, Malay Seals